Stabilitas Ekstrak Pewarna Daun Singkong (Manihot esculenta C.) Pada Perlakuan pH Awal dan Suhu Penyimpanan - Anggraeni, Sinta; Wartini, Ni Made; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2023)
Cassava leaves are leaves that can be used as a source of natural dye. Cassava leaves have a fairly high chlorophyll content and can be extracted into green dye extract. This study aimed to determine how the stability of the cassava leaf dye extract at the initial pH treatment and storage temperature and to determine the initial pH and temperature that provide the best stability to the cassava leaf dye extract during storage. This experiment  used a completely randomized design with two factors. The first factor is the initial pH which consists of pH 9, pH 10 and pH 11. The second factor is the storage temperature consisting of cold temperature (8±2ºC) and room temperature (28±2ºC). The data were analyzed by analysis of variance to determine the effect of treatment on the observed variables. The results showed the initial pH and temperature treatment during storage and their interactions affected the total chlorophyll content, chlorophyll a content, chlorophyll b content, antioxidant capacity, brightness level value (L*), redness level value (a*) and yellowness level value ( b*) cassava leaf coloring extract. Cassava leaf dye extract was most stable at initial pH 9 and cold temperature (8±2ºC) during storage. Storage of cassava leaf dye extract for 7 days caused a decrease in total chlorophyll content of 4 8.44%, chlorophyll a by 46.86%, chlorophyll b by 49.35%, antioxidant capacity by 30.87%, redness level value (a*) by 62.91%, but caused an increase in  the value of the redness level (a*) of 62.91% , the value of the brightness level (L*) of 29.28% and the value of the yellowness level (b*) of 49.02% against the control.